Current advancements in the mechanisms and animal models of acute exacerbation of pulmonary fibrosis: a systematic review - Chen, Kai; Zhang, Hailong; Yao, Zhaoxu; Tao, Siyu; Ma, Qian (Frontiers in Pharmacology, 2025)
Characterized by sudden onset, accelerated disease progression, and high mortality rates, acute exacerbation (AE) represents the most critical clinical challenge faced by patients with idiopathic pulmonary fibrosis (IPF). The absence of standardized animal models that recapitulate human disease phenotypes remains a significant impediment to the study of AE-IPF. In this work, we conducted a systematic review of experimental protocols for acute exacerbation of pulmonary fibrosis (AE-PF) over the past 20 years relating to aspects such as animal species, drugs, drug doses, drug administration routes, and model characteristics, and summarized research progress on the mechanism underlying this condition. Statistical analysis revealed that bleomycin combined with lipopolysaccharide represents the predominant experimental paradigm for AE-PF, accounting for 26.3% (5/19) of all AE-PF models. Our analysis further showed that the major mechanisms involved in AE-IPF are inflammation, immune imbalance, oxidative stress, endoplasmic reticulum (ER) stress, and apoptosis of alveolar epithelial cells.